Translating Nepal’s National AI Policy into Action: Strategic Roadmap for Education, Industry, Infrastructure, and Digital Diplomacy - Pandeya, Yagya Raj; Bhatt, Bhaskar (Api Journal of Science, 2025)
Artificial intelligence is fundamentally transforming Nepal's socio-economic landscape, with far- reaching implications across diverse sectors. Recognizing this transformative potential, the Government of Nepal published an AI Concept Paper in2024, followed by the National AI Policy in 2025. However, translating policy frameworks into tangible outcomes requires developing comprehensive short-term and long-term AI strategies that deliver public value. Education, digital infrastructure, industry, and digital diplomacy emerge as pivotal sectors where AI can advance national interests, accelerate sectoral development, and address critical cybersecurity challenges. This study examines AI-driven opportunities and risks across four key domains: industrial value chains, education, digital infrastructure, and digital diplomacy. Each sectoral analysis explores current conditions, potential use cases, associated risks, and emerging opportunities for AI integration. This study employed a multi-method approach combining extensive desk reviews, iterative report evaluations, focused group discussions, and stakeholder consultations. This methodology incorporates diverse perspectives and draws upon global best practices in AI adoption to ensure comprehensive and contextually relevant findings. The study reveals that each sector requires a holistic and adaptive framework that integrates customized AI implementation strategies, proactive risk management strategies, sustainable funding mechanisms, and robust evaluation systems. Critical priorities identified across sectors include enacting data privacy legislation, investing in workforce upskilling programs, developing essential digital infrastructure, implementing AI risk mitigation protocols, strengthening digital diplomacy capabilities, and enhancing cybersecurity measures. These interconnected priorities collectively shape Nepal's evolving position within the global AI ecosystem and determine its capacity to leverage AI for inclusive development. This study provides policymakers with strategic insights, evidence-based analysis, and practical implementation tools to formulate effective AI policies, address critical infrastructure and governance gaps, and foster inclusive capacity building across sectors.